Technological pedagogical content knowledge, commitment and motivation of physics teachers to implement online teaching and learning during covid-19 pandemic - Samsul Juwait; Siew Nyet Moi @ Sopiah Abdullah; Mad Noor Madjapuni (Secholian Publication, 2022)
Most educational institutions were closed as one of the measures to deal with the COVID-19 pandemic. Teachers are mobilized to adapt online teaching and learning (OTL) methods to continue the educational process. However, previous studies have found that teacher motivation is affected due to this pandemic. Therefore, a quantitative study using questionnaire was conducted to examine the influence of Technological Pedagogical Content Knowledge (TPACK) and commitment on Physics teachers' motivation to implement OTL. A total of 77 male and 109 female Physics teachers in Sabah were selected using a stratified random sampling method. Descriptive analysis using SPSS found that teachers' level of TPACK, commitment, and motivation in implementing OTL is high. Multiple regression analysis found that the constructs of Content Knowledge and Technological Pedagogical Content Knowledge in TPACK have a significant relationship and influence on the motivation to implement OTL. The commitment constructs: Commitment to School, Commitment to Teaching, and Commitment to Profession, were also found to have a significant relationship and influence on the motivation to implement OTL. This study is helpful to stakeholders in understanding the situation of Physics teachers while carrying out essential tasks in the context of the Covid-19 pandemic to formulate relevant policies and programs for the survival of the national education system.